Pengaruh Performance Expectation, Effort Expectation, Social Influence, dan Facilitating Condition terhadap Behavioral Intention pada Pengguna ShopeePay di Jakarta - By Venansius Kenny; Carunia Mulya Firdausy (Universitas Tarumanagara, 2022)
The behavioral intention of e-wallet users has increased significantly today. This study aims to analyze the influence of performance expectation, effort expectation, social influence, and facilitating conditions on the behavioral intention of ShopeePay users in Jakarta. Methods used to collect the data were by distributing questionnaires as an instrument to one hundred respondents who did their transactions by using ShopeePay in Jakarta. The data was then analyzed by applying the Partial Least Squares (PLS) statistical method. The result showed that the behavioral intention of users who used ShopeePay was influenced by performance expectation, effort expectation, social influence, and facilitating conditions. Therefore, the ShopeePay company needs to pay attention to these four variables to improve the behavioral intention of its users. Behavioral intention dari pengguna dompet digital telah meningkat secara signifikan saat ini. Penelitian ini bertujuan untuk menganalisis pengaruh performance expectation, effort expectation, social influence, dan facilitating condition terhadap behavioral intention pengguna ShopeePay di Jakarta. Metode yang digunakan untuk mengumpulkan data adalah dengan menyebarkan kuesioner sebagai instrumen kepada seratus responden yang melakukan transaksi dengan menggunakan ShopeePay di Jakarta. Data tersebut kemudian dianalisis dengan menggunakan metode statistik Partial Least Squares (PLS). Hasil penelitian menunjukkan bahwa behavioral intention pengguna yang menggunakan ShopeePay dipengaruhi oleh performance expectation, effort expectation, social influence, dan facilitating condition. Oleh karena itu, perusahaan ShopeePay perlu memperhatikan keempat variabel ini untuk meningkatkan behavioral intention penggunanya.